Anatomical description of the salivary glands: parotid, mandibular and sublingual of the crab-eating-fox (Cerdocyon thous) (Acta Scientiarum. Biological Sciences, 2018)
Descriptive anatomical studies of wild animals are fundamental, since they provide subsidies for the elaboration of more adequate techniques of sustained management, contributing to the preservation of species threatened with extinction. Thus, the aim of the study is to anatomically describe the salivary glands: parotid, mandibular and sublingual of the crab-eating-fox (Cerdocyon thous). For this purpose, three carcasses of crab-eating-fox donated by Ibama were used. The animals were fixed with 10% aqueous formaldehyde solution, dissected, analyzed descriptively and photographed. It was found that the parotid gland of the crab-eating-fox is located caudally to the branch of the mandible, in the rostroventral margin of the auricular cartilage.  The mandibular gland is located in the atlantal fossa and extends to the basi-hyoid bone. The sublingual gland of the crab-eating-fox shows two parts: monostomatic and polystomatic. The monostomatics are located in the occipitomandibular region of the digastric muscle and the portion polysomatic is situated between the tunica mucosa of the oral cavity and the buccinator muscle. Based on the results, we conclude that the salivary glands of the crab-eating-fox are found distributed in the facial region and present anatomical characteristics that follow the same structural pattern described for other species of carnivorous mammals.